2018
DOI: 10.3346/jkms.2018.33.e140
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress and Drawing Tests among Women with Breast Cancer

Abstract: BackgroundThe aim of this study was to evaluate the use of the Diagnostic Drawing Series (DDS) as a screening tool for the breast cancer patients with psychological distress.MethodsAll of 64 patients with breast cancer participated in this study. Patients' depressive and anxiety symptoms were assessed using Patient Health Questionnaire-9 (PHQ-9) and Generalized Anxiety Disorder-7 (GAD-7) when the DDS was applied to the partipicants.ResultsDepressed patients used more enclosure in the Feeling drawings (P = 0.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Similar the previous study, 22 enclosure in DFA was associated with depression. The DFA has separate check boxes to evaluate enclosure and surrounded, but we unite those two items as a single item of Surrounded, since symbolic meanings of both items were similar in art therapy psychological and physical defense.…”
Section: Surroundedsupporting
confidence: 90%
See 3 more Smart Citations
“…Similar the previous study, 22 enclosure in DFA was associated with depression. The DFA has separate check boxes to evaluate enclosure and surrounded, but we unite those two items as a single item of Surrounded, since symbolic meanings of both items were similar in art therapy psychological and physical defense.…”
Section: Surroundedsupporting
confidence: 90%
“…If the lines were short, lacking pen pressure, or if no lines were used in the drawing, it was deemed to be a drawing response characteristic of a depressed patient, and was scored as 1. Based on the study by Kim et al [ 22 ], breast cancer patients with depression showed mostly moderate pen pressure, unlike psychiatric patients with depression. Pen pressure was classified into three levels with the following scores: weak pen pressure=1, medium pen pressure=0.5, and strong pen pressure=0.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations